Defining and understanding the "extra‐corporeal membrane oxygenation gap" in the veno‐venous configuration: Timing and causes of death. Issue 3 (7th September 2021) - Heuts, Samuel; Makhoul, Maged; Mansouri, Abdulrahman N.; Taccone, Fabio Silvio; Obeid, Amir; Belliato, Mirko; Broman, Lars Mikael; Malfertheiner, Maximilian; Meani, Paolo; Raffa, Giuseppe Maria; Delnoij, Thijs; Maessen, Jos; et al.
Abstract: In‐hospital mortality of adult veno‐venous extracorporeal membrane oxygenation (V‐V ECMO) patients remains invariably high. However, little is known regarding timing and causes of in‐hospital death, either on‐ECMO or after weaning. The current review aims to investigate the timing and causes of death of adult patients during hospital admittance for V‐V ECMO, and to define the V‐V ECMO gap, which is represented by the patients that are successfully weaned of ECMO but still die during hospital stay. A systematic search was performed using electronic MEDLINE and EMBASE databases through PubMed. Studies reporting on adult V‐V ECMO patients from January 2006 to December 2020 were screened. Studies that did not report on at least on‐ECMO mortality and discharge rate were excluded from analysis as they could not provide the required information regarding the proposed V‐V ECMO‐gap. Mortality rates on‐ECMO and after weaning, as well as weaning and discharge rates, were analyzed as primary outcomes. Secondary outcomes were the causes of death and complications. Initially, 35 studies were finally included in this review. Merely 24 of these studies (comprising 975 patients) reported on prespecified V‐V ECMO outcomes (on‐ECMO mortality and discharge rate). Mortality on V‐V ECMO support was 27.8% (95% confidence interval (CI) 22.5%‐33.2%), whereas mortality after successful weaning was 12.7% (95% CI 8.8%‐16.6%, defining the V‐V ECMO gap ). 72.2% of patients (95% CI 66.8%‐77.5%) were weaned successfully from support and 56.8% (95% CI 49.9%‐63.8%) of patients were discharged from hospital. The most common causes of death on ECMO were multiple organ failure, bleeding, and sepsis. Most common causes of death after weaning were multiorgan failure and sepsis. Although the majority of patients are weaned successfully from V‐V ECMO support, a significant proportion of subjects still die during hospital stay, defining the V‐V ECMO gap . Overall, timing and causes of death are poorly reported in current literature. Future studies on V‐V ECMO should describe morbidity and mortality outcomes in more detail in relation to the timing of the events, to improve patient management, due to enhanced understanding of the clinical course. Abstract : Graphical abstract present the V‐V ECMO gap. In 24 studies comprising 975 patients, on‐ECMO mortality was 27.8%, while 72.2% of patients were weaned successfully. Still 12.7% of patients deceased after weaning, defining the proposed V‐V ECMO gap.